Optimalisasi Program Kampus Mengajar 6 Melalui Literasi Numerasi Dengan Pendekatan Bermain Pada Siswa Di SDN Kedungdoro V Surabaya - Reza Maharani Putri Tizaka; Hasan Ismail (Jurnal Informasi Pengabdian Masyarakat, 2024)
Education plays a crucial role in shaping the character and quality of a nation's human resources. This community service program addresses the challenges of numeracy literacy at SDN Kedungdoro V Surabaya and involves the implementation of the Edugame program as an effort to enhance students' interest and understanding of numeracy literacy. The program evaluation reveals several significant findings, indicating the need to improve students' understanding of numeracy literacy. Nevertheless, the program successfully increased student participation, strengthened collaboration within groups, and created an enjoyable learning atmosphere. The in-depth evaluation involves analyzing student involvement, numeracy literacy understanding, and the achievement of learning goals. Challenges in organizing students, the lack of parental attention, and students' difficulties in understanding numeracy literacy concepts are identified as obstacles in the community service process. The conclusion emphasizes that collaboration between educational institutions, students, and parents is key to strengthening numeracy literacy, with a commitment to continuously improve the program for optimal results.